Magnetic sentinel node and occult lesion localization in breast cancer (MagSNOLL Trial). Issue 6 (May 2015) - Ahmed, M.; Anninga, B.; Goyal, S.; Young, P.; Pankhurst, Q. A.; Douek, M.; the MagSNOLL Trialists Group; Hamed, H.; Kothari, A.; Kovacs, T.; McWilliams, S.; Monypenny, I.; et al.
<x xml:space="preserve">Abstract</x> Background Non‐palpable breast cancers require localization‐guided surgery and axillary staging using sentinel lymph node biopsy (SLNB). This study investigated the novel technique of magnetic‐guided lesion localization and concurrent SLNB, which avoids the need for wire‐guided localization and radioisotopes. Methods An ultrasound‐guided intratumoral injection of magnetic tracer (0·5 ml) was performed in a protocol‐driven predefined minimum of ten patients with palpable breast cancer to assess the ability of the magnetic tracer safely to localize the tumour at the site of injection and concurrently drain to the lymphatics. Once successful lesion localization had been confirmed (peak magnetometer count retained at the centre of the tumour), the technique was undertaken in a further 20 patients with non‐palpable breast cancers awaiting wide local excision and SLNB. All patients underwent SLNB with both the magnetic and standard dual (radioisotope and Patent Blue V dye) techniques. Results Thirty‐two patients were recruited, of whom 12 (1 with bilateral disease) presented with palpable and 20 with non‐palpable breast cancer. Peak magnetometer counts were retained at the tumour centre in all palpable (13) and non‐palpable (20) breast cancers. Re‐excisions for involved margins were necessary in two patients with non‐palpable breast cancers. The sentinel lymph node identification rates were 28 of 33 procedures for the magnetic technique alone, 32 of 33 for the magnetic technique combined with blue dye, and 32 of 33 for the standard dual technique. Conclusion Magnetic lesion localization is feasible, with intratumoral magnetic tracer injection combined with a periareolar injection of blue dye for subsequent SNLB.